Outpatient group therapy for post-COVID patients - a naturalistic feasibility study of a face-to-face and online group concept - Zimmermann-Schlegel, Verena; Gronewold, Nadine; Stengel, Sandra; Hartmann, Mechthild; Merle, Uta; Friederich, Hans-Christoph; Ditzen, Beate; Tesarz, Jonas (Frontiers in Psychiatry, 2024)
BackgroundA significant number of individuals diagnosed with SARS-CoV-2 continue to suffer from persistent symptoms, a condition commonly referred to as Post-COVID syndrome (PCS). The most common manifestations are fatigue, post-exertional malaise, respiratory problems and cognitive deficits due to the lack of a causal treatment, therapeutic options remain symptom oriented. The aim of this study was to develop a low-threshold group therapy concept for patients with PCS and to test its feasibility in face-to-face and online format.MethodAn interprofessionally oriented group therapy concept for patients with PCS was developed and a treatment manual was established. The concept comprises eight weekly sessions of 90 minutes each, during which the management of fatigue, stress intolerance and other symptoms are addressed and coping strategies are discussed and developed. The group therapy was conducted alternating in face-to-face and online format and evaluated via questionnaires.ResultsA total of 57 patients, most of them with severe limitations due to PCS, took part in the groups (n=36 online; n=21 face-to-face). The group offer was requested and accepted in both the face-to-face and online formats, and was predominantly evaluated as beneficial. Of particularly value was the opportunity to engage with peers who share similar experiences.ConclusionThe interprofessional, integrative psychotherapeutic/psychoeducational group therapy is safe, accepted and is predominantly rated as helpful by participants. It should be carried out in online formats for patients with PCS who are limited in mobility. Controlled studies are necessary to further evaluate the proposed concept and its integration into the care landscape.